Implementasi Pembelajaran Terpadu di Sekolah Dasar Islam Terpadu Ikhtiar Makassar - S, Muh. Risal (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to examine the implementation of the TERPADU learning strategy at SDIT Ikhtiar Makassar, an Islamic integrated elementary school that combines the national curriculum with Islamic values. The research subjects included the principal, teachers, and students who were directly involved in the teaching and learning process. The study employed a qualitative descriptive method, and data were collected through interviews, observations, documentation, and questionnaires. Data analysis was carried out through the stages of data reduction, data presentation, and inductive conclusion drawing. The findings indicate that the TERPADU strategy comprising the stages of Telaah (Study), Eksplorasi (Explore), Rumuskan (Formulate), Presentasikan (Present), Aplikasikan (Apply), Duniawi (Worldly), and Ukhrowi (Spiritual)—has been systematically implemented in both curricular and extracurricular activities. This approach has significantly contributed to the improvement of students' cognitive learning outcomes, as evidenced by increased average academic scores, higher bilingual program achievements, and improved graduation rates. In addition, the strategy has promoted students’ character development in the affective domain, such as discipline, independence, and consistency in worship. These findings affirm that TERPADU is not merely an instructional method, but a transformative educational paradigm that fosters intellectually capable and spiritually grounded students.